Best Proximity Points and Fixed Points Results for Noncyclic and Cyclic Fisher Quasi-contractions. (4th April 2019) - Safari-Hafshejani, Akram; Amini-Harandi, Alireza; Fakhar, Majid
Abstract: In this article, in the setting of metric spaces we introduce the notions of noncyclic and cyclic Fisher quasi-contraction mappings. We establish the existence of an optimal pair of fixed points for a noncyclic Fisher quasi-contraction mapping and iterative algorithms are furnished to determine such optimal pair of fixed points. For a cyclic Fisher quasi-contraction mapping, we also study the existence of best proximity points. Presented results extend and improve some recent results in the literature.